A Parallel Tableau Algorithm for BIG DATA Verification - Asteasuain, Fernando (2020)
Big data systems are becoming more and more present in our everyday life generating data and information that needs to be explored and analyzed. In this sense, formal verification tools and techniques must provide solutions to face with these new challenges since they been pointed out as one of the most needed software engineering activities to consolidate big data modern systems. In this work we present a parallel implementation of a tableau algorithm aiming to improve the performance of our formal verification scheme. The pursued objective behind this transformation is to adapt our framework to deal with big data systems.